Research on Fault Location in Distribution Network Based on Fast Fault Transfer Arc Extinguishing Device. Issue 1 (November 2020) - Xinyu, Zhang; Yu, Nie; Yanan, Wang; Dan, Zhao; Wei, Du; Zimo, Zheng
Abstract: In the distribution network equipped with fast fault transfer arc extinguishing device, after a single-phase grounding fault occurs, the fault phase bus is quickly grounded to realize arc extinguishing. At the same time, the traveling wave signal generated during the grounding process of the fault phase bus can realize fault location. The traveling wave signal is subjected to phase-mode transformation, and the time difference of the zero-mode component mutation detected twice at the exit of the fault line is to be recorded. This time difference is the time which it takes for the zero-mode component to go to and fro once between the bus and the fault point. And then the fault distance can be calculated based on it. The integration of arc extinguishing and fault location is realized. The AT P simulation software is used to realize the fault simulation of distribution network. And the accuracy and feasibility of the proposed fault location method are verified.